Effects of communication strategies on UP Mindanao OSA-SOAS information transfer - Diaz, Danielle G.
This study is concerned with the communication strategies used by UP Mindanao OSA-SOAS and its effects on the information transfer of the unit. It recognizes the role of communication in the fulfillment of OSA-SOAS function. Information transfer is documented by Auditing Communication Strategies, Key Information Interviews, and Focus Group Discussion (FGD). The audit revealed the level of maturity of OSA-SOAS communication strategies and associates it with student organization feedback through FGDs. The FGD also revealed student observations regarding identified communication methods with identified strengths and weaknesses, identified factors that affect student response and cooperation, student reception toward OSA-SOAS and student organizations? processing of information. Students response and factors that affect response were analyzed through Organizational Information Theory and Network Theory, Organization Information Theory explained how student organizations process information with the goal to gather information, understand it and make decisions based on understood information creating knowledge through reduction of equivocality. The Network Theory helped identify networks existing in the knowledge process of OSA-SOAS. Identified networks were OSA-SOAS, student organization and personal networks. The study identified the role of organization heads as primary links of OSA-SOAS to student organization and its use of formal and emergent networks. The section uses near transfer to transfer knowledge to its stakeholders and the use of exper transfer to reduce equivocality. The study was grounded on the environment of the information transfer through problem tree analysis.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication